(untitled) (Innovate Conferences, 2025)
Regions play an important role in the development of small business. It is local authorities who know exactly the financial and material capabilities of their territory, the real needs of the population for certain types of products and services, and ways to effectively use resources in the form of ownership and areas of activity from the regional point of view. As our country’s experience in using the influence of local authorities in the development of business structures shows, in recent years, a sufficiently serious development of entrepreneurship has been ensured.